New Co(II), Cu(II) and Ni(II) complexes with TOKMAK1,2-bis(o-aminophenoxy) ethane - Tokmak, N.; Şekercui, M.; Temel, H. (My University, 2006)
1,2-Bis(o-aminophenoxy)ethane was prepared in a one stage process. In this reaction, Pd/C was used as catalyst 1,2-Bis(o-aminophenoxy)ethane was synthesized from 1,2-bis(o-nitrophenoxy)ethane. Diamine complexes [CoLCl 22H2O], [CuLCl2]0.5H2O and [NiL 2(C2H5O)2] have been synthesized and characterized by elemental analyses, ?M, IR, UV-VIS, 1H NMR and magnetic measurements.